2010
DOI: 10.1111/j.1744-6171.2010.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Among Maternal BMI, Family Factors, and Concern for Child's Weight

Abstract: results suggest the importance in understanding the family and community and its influence on childhood obesity. Armed with knowledge about family factors and parents' beliefs and perceptions, nurses can develop interventions that can assist families and communities to focus on healthy children feeding and weight management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(29 reference statements)
0
12
2
Order By: Relevance
“…In a study of family dynamics and BMI in families with children aged 12 to 17, Cyril et al found that family functioning, which is a measure of the quality of interactions between members of a family, was inversely associated with child BMI, but no associations were found with parent BMI. Similarly, a mother‐child study by Payas et al also found no associations between family functioning and mothers’ BMI. This discrepancy between our findings and those of studies exploring family functioning suggests that CHAOS is measuring a distinct construct, and future research should explore the mechanisms by which CHAOS in the household influences obesity risk.…”
Section: Discussionmentioning
confidence: 92%
“…In a study of family dynamics and BMI in families with children aged 12 to 17, Cyril et al found that family functioning, which is a measure of the quality of interactions between members of a family, was inversely associated with child BMI, but no associations were found with parent BMI. Similarly, a mother‐child study by Payas et al also found no associations between family functioning and mothers’ BMI. This discrepancy between our findings and those of studies exploring family functioning suggests that CHAOS is measuring a distinct construct, and future research should explore the mechanisms by which CHAOS in the household influences obesity risk.…”
Section: Discussionmentioning
confidence: 92%
“…It is well established in the literature that overweight/obese mothers are less likely to breastfeed at all or exclusively . Maternal obesity has also been associated with feeding beliefs and practices that may promote later obesity in older children . It was therefore hypothesised that maternal weight status is also likely to play a role in early maternal feeding beliefs and practices.…”
Section: Discussionmentioning
confidence: 99%
“…28 Maternal obesity has also been associated with feeding beliefs and practices that may promote later obesity in older children. 9,13,14,24 It was therefore hypothesised that maternal weight status is also likely to play a role in early maternal feeding beliefs and practices. The results of this study did not support this hypothesis, indicating no significant differences in maternal feeding beliefs and practices reported by healthy weight and overweight women, independent of feeding mode (fully breastfeeding vs. mixed/formula feeding only), during the first 4 months of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations